ANALISIS KUALITAS PELAYANAN PADA PT ASTRA INTERNASIONAL DAIHATSU â€“ DSO MALALAYANG - Jofani Nicky Charolin Senewe; Harry J. Sumampouw; Sonny. G. Kaparang (JURNAL ADMINISTRASI BISNIS, 2017)
Abstract. The development and improvement of services in the field of automotive companies over the years increasingly become the public's attention. It can be seen from the intense competition among the many service quality automotive companies. In conditions of intense competition, the main thing that should be prioritized by the automotive company is concerned with customer satisfaction in order to survive, compete, and market share. This study was conducted to determine how the quality of existing services at PT Astra International Daihatsu-DSO Malalayang. The method used in this research is survey method, the research took a sample of the population and the use of a questionnaire as a data collection tool. And a sample of 60 customers who responded to the statements about the dimensions of service quality. Data were analyzed using analysis of TERRA, which analyzes the quality of service using dimensional analysis of tangibles (direct evidence), empathy (empathy), reliability (reliability), responsiveness (responsiveness) and assurance (guarantee). The results were obtained S <1, it indicates that the degree of correspondence between the performance of services (service performance) and consumer expectations (customer expectation) has not reached the peak of maximum satisfaction .Â  Keywords: Service Performance, Customer Expectation